Effect of wavy wall surface on flow structure and thermal characteristics of a turbulent dual jet comprising of a wall jet and an offset jet - Singh T.P.; Kumar A.; Satapathy A.K. (My University, 2025)
The fluid flow and thermal characteristics of the dual jet are explored numerically. The dual jet is considered with a wavy wall surface having various amplitudes varying between 0.1 and 0.7 with a fixed number of cycles equal to 10. The offset ratio is also varied from 3 to 15 with an interval of 2. The Reynolds number and Prandtl number are set to 15,000 and 0.71, respectively. The Semi Implicit Method for Pressure Linked Equation algorithm is utilised to link the pressure to the velocity. To solve the set of linear algebraic equations Strongly Implicit procedure solver is used. The heat transfer characteristics of the wavy wall surface were studied for two cases: (1) isothermal bottom wall and (2) adiabatic bottom wall. It is found that the wavy wall affects the flow field and heat transfer characteristics drastically. The minimum pressure inside the domain is not found to occur at the vortex centre for all the offset ratios, which is the case of a dual jet with a plane wall. Results also reveal that as the amplitude of the wavy surface increases both local Nusselt number and local heat flux increase near the exit of the nozzle for each offset ratio. Further, it is also noticed that the average Nusselt number increases up to amplitude A = 0.5. Thereafter, it decreases with further increase in the amplitude of the wavy surface. It is found that the wavy surface increases the average Nusselt number by a maximum of 17.6% as compared to the plane wall case. © IMechE 2020.